Cell-Free Regenerative Therapy for Pulmonary Hypertension: Human Breastmilk Stem Cell Secretome Restores Endothelial Barrier Integrity and BMPR2 Signaling Under Hypoxic Stress - Sri Lilijanti Widjaja; Mylco Trisaputa Ahmadwirawan; Dina Luthfiyah (HM Publisher, 2026)
Background: Pulmonary hypertension (PH) is a severe vascular disorder characterized by chronic hypoxia-induced endothelial dysfunction, leading to aberrant remodeling and right ventricular failure. The human breastmilk-derived stem cell (hBSC) secretome contains bioactive factors that may promote endothelial regeneration. However, the temporal dynamics of secretome-mediated repair on critical structural and signaling molecules remain poorly understood. Methods: An in vitro experimental study was conducted using human umbilical vein endothelial cells (HUVECs) exposed to severe hypoxia (1% O₂, 10% CO₂, 37°C) to replicate PH-associated endothelial dysfunction. Cells were divided into four groups: normoxia control, hypoxia control, and hypoxia treated with hBSC secretome for 24 and 72 hours. Expression of bone morphogenetic protein receptor type 2 (BMPR2) and vascular endothelial cadherin (VE-cadherin) was quantified via ELISA. CCK-8 assays evaluated cellular viability. Data were analyzed using one-way ANOVA and least significant difference (LSD) post-hoc tests. Results: Hypoxia significantly diminished cell viability and reduced BMPR2 and VE-cadherin expression compared to normoxia (p<0.001). Administration of hBSC secretome significantly restored BMPR2 and VE-cadherin levels at both 24 and 72 hours (p<0.001), surpassing normoxic baselines. BMPR2 expression plateaued between 24 and 72 hours, while VE-cadherin expression demonstrated sustained functional recovery. Conclusion: The hBSC secretome actively reverses hypoxia-induced endothelial injury through rapid, time-dependent modulation of BMPR2 signaling and VE-cadherin junctional integrity, presenting a viable cell-free therapeutic target for PH.